Digital Adaptation Strategies for Enhancing MSME Resilience Against Extreme Weather in Urban Contexts - Ariwangsa, IGN Oka; Putra P, Komang Widhya Sedana (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
More frequent extreme weather conditions disrupt urban ecosystems and the sustainability of MSMEs, crucial contributors to the local economy. This paper seeks to explore extreme weather conditions' impacts on MSMEs in Denpasar, Indonesia, and the mitigation role of digital technologies using IoT and GIS for environmental risk mitigation. This study employs a quantitative approach by using PLS-SEM in order to analyze the interactions between extreme weather, digital adaptation strategies, and the sustainability of MSMEs. It was found that extreme weather negatively impacts the operation and financial stability of MSMEs, while digital adaptation strategies have significantly improved their resilience and sustainability. The originality of this study lies in integrating resilience theory and technological determinism to address the challenges of urban MSMEs. Recommendations on how to strategically facilitate digital transformation to enhance operational efficiency for sustainable urban development are provided